Research on the Basic Ability Training of Maritime Professional Talents under the Background of Smart Port Development - Hou, Qiuping (Education Insights, 2026)
Against the backcloth of uninterrupted overlap between -generation information technologies include IoT, big datum, thereby and AI, smart port development has emerge as a pivotal driver for mellow-quality growth in the shipping industry. The and shift of port operations has lift new, high-level requirements for marine professional' foundational competence, hence this work employs literature analysis. Questionnaire surveys. And case studies to systematically delineate the core competency framework for marine professional in saucy port contexts. Build on an analysis of wise port development and virtual overture to talent cultivation, it describe key challenge in current training programs and suggest targeted optimization strategies. Through substantiation expend case studies from leading institutions, this inquiry aims to provide theoretic credit and pragmatic penetration for elaborate maritime talent development systems, aline with impudent port requirements. And fostering integrating between educational and industrial ecosystem.